Exploring the Genetic Diversity of Mycoplasma hyopneumoniae in Pigs with Pneumonia and Pleurisy at Slaughter - Panneitz, Ana Karolina [UNESP]; Braga, Eduarda Ribeiro [UNESP]; Petri, Fernando Antonio Moreira [UNESP]; Menegatt, Jean Carlo Olivo; Driemeier, David; Maes, Dominiek; Oliveira, Luís Guilherme de [UNESP] (MDPI, 2024)
Mycoplasma (M.) hyopneumoniae is the key pathogen of the porcine respiratory disease complex (PRDC) and contributes to pleurisy in pigs. Due to its limited metabolism and laborious cultivation, molecular tools are useful for diagnosis. This study investigated the genetic diversity of M. hyopneumoniae in slaughter pigs with pneumonia and pleurisy, and it assessed co-infections by Pasteurella multocida type A (PM), Actinobacillus pleuropneumoniae (APP), and swine influenza virus A (sIVA). Lungs (n = 70) with different pleurisy scores and lesions compatible with M. hyopneumoniae infection were collected for convenience. Macroscopic and microscopic evaluations were performed. M. hyopneumoniae was detected using qPCR, and MLST was used for genetic characterization. Co-infections with PM and APP were also evaluated by qPCR, while the immunohistochemistry assessed sIVA infection. All lungs were positive for M. hyopneumoniae. Histopathology confirmed M. hyopneumoniae-associated lesions. MLST characterization was possible in 25 lungs and revealed 10 distinct allelic profiles, with none matching known sequence types in the public database. Co-infections were detected in 40% of the samples with APP and 32% with PM, with 12% showing both pathogens and 52% of the samples presenting microscopic lesions compatible with sIVA infection. The diverse genetic profiles found underscore the need for research on isolation and potential pathogenic variations.
Keywords: alleles; BALT hyperplasia; MLST; pneumonia; porcine enzootic pneumonia; respiratory disease